The influence of forest management on boreal forest structure and microclimate - Starck, Iris (Helsingin yliopisto, 2025)
Forest management alters the three-dimensional structure of boreal forests, affecting light regimes, microclimate, and habitat availability, which contribute to regulating biodiversity and ecosystem functions. The reduction in temporal fluctuations of microclimate temperatures compared to open-air temperature, referred to here as microclimatic buffering, plays a crucial role in mitigating temperature extremes under canopies, providing stable environments that support forest organisms under changing climatic conditions. However, the resilience of these ecosystems is increasingly threatened by the combined effects of climate warming and intensive management. While even-aged rotation forestry has dominated Fennoscandia since the mid-20th century, continuous cover forestry has recently emerged as a potential alternative for fostering structurally heterogeneous and resilient forests. However, the impacts of these management approaches on the ability of forests to regulate local climate conditions (i.e., the microclimate) remain inadequately quantified. This thesis aims to quantify how different forest management practices influence structural variability and microclimatic buffering in boreal forests using ground-based 3D laser measurements, in-situ microclimate data, open geospatial forest data, and modern statistical and machine-learning approaches. The first chapter of the thesis used terrestrial laser scanning to characterize the three-dimensional structural differences between even-aged and uneven-aged forests, the latter being an application of continuous cover forestry. The second chapter integrated this structural information with microclimate data to assess the microclimatic buffering capacities—quantified by the relationship between forest and clear-cut temperatures—of the two management types and identify the structural characteristics that drive buffering. The third chapter upscaled the analysis to estimate the spatial variation of microclimatic buffering across Finnish forestry land and its biogeographic ...